2013
DOI: 10.1103/physrevlett.110.168106
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence and Survival in Conservative Lotka-Volterra Networks

Abstract: Analyzing coexistence and survival scenarios of Lotka-Volterra (LV) networks in which the total biomass is conserved is of vital importance for the characterization of long-term dynamics of ecological communities. Here, we introduce a classification scheme for coexistence scenarios in these conservative LV models and quantify the extinction process by employing the Pfaffian of the network's interaction matrix. We illustrate our findings on global stability properties for general systems of four and five specie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
100
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 54 publications
1
100
0
Order By: Relevance
“…Indeed, several recent works (e.g., Refs. [23,42,43,48]) have shown that the structure of the interaction graph alone is not enough to predict the asymptotic temporal evolution of the system, stressing the importance of the invasion rates.…”
Section: Model Dynamics and Network Topologymentioning
confidence: 99%
“…Indeed, several recent works (e.g., Refs. [23,42,43,48]) have shown that the structure of the interaction graph alone is not enough to predict the asymptotic temporal evolution of the system, stressing the importance of the invasion rates.…”
Section: Model Dynamics and Network Topologymentioning
confidence: 99%
“…Similar studies of more complicated systems composed of multiple species interacting in less trivial ways have been scarce until recently [61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77].…”
Section: Introductionmentioning
confidence: 99%
“…Much work has been devoted to cyclic cases as for example the three-species cyclic game [21] or the corresponding game with four species where each species is preying on one other species while being at the same time the prey of another species [22][23][24][25][26][27][28][29]. Whereas some earlier papers have considered spatial and stochastic effects in systems with a larger number of species [30][31][32][33][34][35][36][37][38][39][40][41], it is only in the last few years that systematic theoretical studies of more complicated food networks with five or more species 2 have become available [19,[42][43][44][45][46][47][48][49][50][51][52][53][54]. One of the intriguing results of these studies has been the discovery of a rich variety of space-time patterns, including spirals where each wavefront is formed by a single species, fuzzy spirals due to the mixing of different species inside the waves, coarsening domains where every domain is formed by an alliance of mutually neutral species as well as coarsening processes where inside every domain spirals are formed, thus yielding non-trivial dynamics inside the coarsening domains [19,48,51,55].…”
Section: Introductionmentioning
confidence: 99%